O jogo protagonizado e a atividade orientadora de ensino: vivências com noções geométricas na educação infantil - Pinto, Lilian Aparecida Borges (2023)
According to Historical-Cultural Psychology, the role-playing game is the main activity of pre-school children, as it promotes the most important psychic changes in this phase. In it, social relations are reconstructed without direct utilitarian purposes, unlike what we are proposing here, when we use the game as a protagonist to provide experiences with geometry. Thus, having the game as the protagonist of the study, we aimed to analyze the possibilities of organizing the game as the protagonist, considering the AOE as a theoretical-methodological basis for the pedagogical activity, involving experiences with geometric notions in Early Childhood Education. The investigation characterized with a qualitative approach was motivated by the search for training for the pedagogical work with mathematics in Early Childhood Education, being guided by the following problem: Possibilities of organization of the game based on the principles of AOE in a pedagogical work with geometric notions. Before delving into the research question, we carried out surveys on CAPES journals and theses and dissertations sites to verify the existence of investigations that dealt with the theme that we intended to address and select references that could be used. During the study, we based ourselves on the Guiding Teaching Activity (AOE) to create the game with the Confectionery theme, which will also constitute an educational product that can be consulted by teachers. When playing the game, we used video recordings, images and notes to capture the information that was later analyzed. In order to establish the units of analysis, we interpreted the information captured in the development of the game with the literature used, the units being defined as follows: perceiving the clay from the senses – touch, sight and smell; elaboration of three-dimensional objects using clay; and creation of drawings two-dimensional shapes from three-dimensional shapes. The results indicate that the organization of the game played according to the assumptions of the AOE provided the children with the opportunity to experience geometric notions. We observed that in the attempt to interpret the roles correctly, there was an effort to solve the triggering situations, thus formulating reflections on the notions that were being developed.